Foraminifers from the Barranca Final Formation (Late Miocene): Paleoecological Inferences - Allende, Aylén (2021)
The Barranca Final Formation was assigned to the Entrerriense or Paranense transgression, based on the foraminifera recovered from its type section, northern coast of the San Matías Gulf, Río Negro province. In this study, we conduct a paleoecological analysis of the foraminiferal assemblages from the type section, including quantitative approaches such as diversity indexes, porcellaneous/agglutinated/hyaline tests ratio, planktonic/benthic ratio and the proportion of infaunal and epifaunal morphotypes.